Taxation of the rich and the cost of raising tax revenue - Geir H. M. Bjertnæs (Statistics Norway, Research Department, 2023)
Taxation of capital income and wealth designed to redistribute from the rich may harm small open economies with a globalized capital market as investments are distorted. This study shows that raising tax revenue by taxing wealth is less costly than by taxing labor income within a simplified model framework designed for modest levels of taxes on capital income and wealth. The explanation is that a recidence based tax on wealth collects tax revenue from wealthy investors without distorting investments. The study also shows that raising tax revenue by increasing the tax rate on capital income marginally above the foreign tax level is less costly than by increasing the tax rate on labor income even though foreign investments is distorted. An assessment of these results together with other empirical and theoretical studies uncover that the cost of taxing capital income and wealth is likely to increase with the level of these taxes, however.
Keywords: H2; H21; F21; 330; Taxation; capital income; wealth